Super Bomb : Organizational Conflict and the Development of the Hydrogen Bomb - Young, Ken, 1943-2019; Schilling, Warner R. (Warner Roller), 1925-2013 (Book collections on Project MUSE., 2019)
"Addresses the question of why President Harry Truman decided to go ahead and develop the H-bomb and with what means dissenters opposed it for several years afterward"--